STREETSCAPE SEBAGAI PEMBENTUK KARAKTER KAWASAN : Studi Kasus : Jalan Rungkut Madya Surabaya - Heru Prasetiyo Utomo; Fairuz Mutia (ATRIUM: Jurnal Arsitektur, 2018)
Title: Streetscape as a Formation of Area Character in Rungkut Madya Street Surabaya Urban areas are always dynamic where some regions develop more rapidly than other regions. Rungkut Madya street as a collector road has undergone many changes along with the construction of MERR road and OERR road plans by the Surabaya City Government and East Java Provincial Government. There is no integration of area arrangement at Rungkut Madya street that is able to characterize and provide visual - spatial quality that is able to improve the physical condition of the area. Meanwhile landscape quality (streetscape) needs to be considered in road design, referring to good streetscape criteria (Moughtin, 1999). The research method chosen is exploratory and descriptive. The description is focused on the authenticity of the shape and character of the area in Rungkut Madya street to explore existing city elements. Data collection more describes the conditions of reality and potential on Rungkut Madya street which are arranged in a mapping. Furthermore, these results are explored using Character Appraisal Research. The analysis is carried out qualitatively and supported by simple quantitative analysis. This research is expected to be able to produce an urban treatment that can identify the quality of the environment to be a special criterion in improving the quality of the environment and the identity of the Rungkut Madya street as an education, trade and service area.